Fertility control in cattle by milk progesterone assay - Καραγιαννίδης, Α. Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
Radioimmunoassay (RIA) of milk progesterone has been used in diary cows for the following purposes: (a) early diagnosis of pregnancy, (b) following up the ovarian function during the ρ ρ period, (c) diagnosis of subfertility and (d) assessment of efficacy of remedial treatments. Pregnancy status predicted from the milk samples taken 21 to 24 days after breeding is 98% accurate for cows not pregnant and 80% accurate for those which are pregnant. In a scrrening program for a p. p. herd fertility, mainly four groups of patterns can be observed: (a) «normal» pattern with onset of some cyclic function wihtin 21 days ρ ρ, (b) normal cyclicity but silent heat, (c) follicular cysts and (d) other acyclic conditions. Under practical conditions sampling frequency for detecting the individual ρ ρ problems has to be minimized. Four alternative applications are offered to farmers, veterinarians and A.I. stations: a) «One-sample test» taken ant day Ο (day of insemination) to discriminate between reliable or non reliable oestrus observation. b) «Two-sample test» (day 0 + day 6) to discriminate additionally between ovulatory oestrus an clinical cases like cysts or acyclic conditions. c) Under optimized management conditions (reliable oestrus observations) the «day 6 only test» may fulfill the same purpose. d) The «three-sample test» (day 0,6 and 20-22) includes the approximate «return or non return» answer. A close relationship exists between milk progesterone concentrations and the palpability of the corpus luteum. Only in cases of cystic follicles being palpated no relationship is seen between progesterone concentrations and clinical findings. Suboestrus cannot be related to any characteristic of the progesterone profile. However, dysfunctionlng of the ovaries is always related to abnormal profiles.